Oligosaccharide Lactate Nanoparticles Enhance Tissue Targeting: A Case Study of the Controlled Delivery of Bedaquiline to Cardiac Tissue in TB Pericarditis - Simisola Ayodele; Pradeep Kumar; Armorel van Eyk; Pieter van der Bijl; Yahya E. Choonara (Molecules)
Bedaquiline is known to shorten the duration of therapy of tuberculosis but has limitations, e.g., poor solubility and adverse effects such as prolongation of the QT interval. In this study, bedaquiline was incorporated into an inherently targeted nanosystem for improved permeation of the drug, with ex vivo diffusion studies performed to investigate its penetration. The bedaquiline-loaded mannan–chitosan oligosaccharide lactate nanoparticles were prepared by a one-step ionic gelation probe sonication method. A PermeGear 7-in-line flow-through diffusion system was used for the ex vivo diffusion studies across porcine and human pericardia. Bedaquiline-loaded nanoparticles with a particle size and potential of 192.4 nm and 40.5 mV, respectively, were obtained. The drug-loaded mannan–chitosan nanoparticles had an encapsulation efficacy of 98.7% and drug loading of 0.6%. Diffusion data indicated a steady-state flux of 2.889 and 2.346 µg.cm−2.min−1 for porcine and human pericardia, respectively. The apparent permeability coefficients were calculated to be 2.66 × 10−4 cm.min−1 and 2.16 × 10−4 cm.min−1 for porcine and human pericardia, respectively. The lag phases were 52.72 min and 0 min for porcine and human pericardia, respectively. The drug permeation indicated a consistent and linear diffusion pattern across both porcine and human pericardia, additionally approving the porcine pericardium as a great comparable tissue to human tissue for pericardial studies. This study is the first to demonstrate ex vivo diffusion of bedaquiline-loaded, macrophage-targeted chitosan–mannan nanoparticles across both human and porcine pericardia, representing a novel platform for disease-targeted, localized treatment of TB pericarditis.